2011
DOI: 10.1590/s0103-73312011000100013
|View full text |Cite
|
Sign up to set email alerts
|

"Circuloterapia": uma metáfora para o enfrentamento da dor crônica em duas clínicas de dor

Abstract: Este artigo descreve e analisa a dinâmica da clínica de dor enquanto um "artefato complexo" do sistema terapêutico biomédico, explorando as múltiplas vozes e as relações dialógicas sobre dor e a interdisciplinaridade no cotidiano clínico de duas clínicas de dor situadas em hospitais-escola nas cidades de Salvador e São Paulo. Foi realizado estudo etnográfico orientado pela antropologia interpretativa, na qual se buscou a descrição de situações singulares e expressivas da dinâmica da clínica de dor (considerada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
(7 reference statements)
0
3
0
6
Order By: Relevance
“…Such fact coincides with other scientific studies when they assert that workers in pain have greater limitation to perform daily activities, 29 such as domestic activities and personal hygiene. 30 In both groups there were relationships between mental functions and domestic life and tasks and demands, which include performing daily routine and dealing with stress and other psychological demands. The psychiatric disorder interferes negatively in the capacity of facing the existing impairments.…”
Section: Discussionmentioning
confidence: 99%
“…Such fact coincides with other scientific studies when they assert that workers in pain have greater limitation to perform daily activities, 29 such as domestic activities and personal hygiene. 30 In both groups there were relationships between mental functions and domestic life and tasks and demands, which include performing daily routine and dealing with stress and other psychological demands. The psychiatric disorder interferes negatively in the capacity of facing the existing impairments.…”
Section: Discussionmentioning
confidence: 99%
“…However, information about users of such health service is still scarce in scientific studies 8 . The interaction between different knowledge and patients' multidisciplinary approach in pain clinics positions them as active subjects in the therapeutic process and provides a holistic vision to professionals, which makes clinical information more detailed and the diagnosis faster 9 . In our study, the sample has shown predominance of females, which reinforces the hypothesis of previous studies which have evidenced higher neuropathic pain prevalence among females 6,[10][11][12] .…”
Section: Discussionmentioning
confidence: 99%
“…A terminologia foi utilizada inicialmente para a dor sentida por pacientes terminais, contudo percebeuse que pode ser aplicada para casos de dor crônica, em que são relatados aspectos mais abrangentes que apenas o fisiológico. Essa compreensão nos fornece uma visão holística de ser humano, ou seja, necessita ser tratado não somente em seu corpo, mas também em seus valores e essência [2][3][4][5][6][7][8][9][10][11][12][13][14]15 .…”
Section: Dorunclassified